Pengenalan Bahasa Bali melalui Media Gending Rare Pada anak Usia Dini di TK Hainan School - Anggreni, Ni Wayan Suci (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2024)
The Balinese language plays a very important role in the life and culture of the Balinese people and has a major role in the intellectual, social and emotional development of students. As one of the local advantages in Bali, learning Balinese is expected to help students get to know, love and help preserve the local advantages of Bali. The introduction of Balinese needs to be intensified. Gending rare not only introduces Balinese language to young children but also forms character traits such as positive values ​​and moral messages. Introduction to Balinese is not only the role of parents at home but can be done at school. The stimulation that can be given to young children in introducing Balinese is similar to the approach used by parents, such as using rare gending media. Through these songs, children can more easily understand and remember their language and culture. Based on this background, several problems that may arise include: (1) What strategies are used to introduce Balinese language through rare gending media in early childhood? (2) what are the inhibiting factors that occur in the introduction of Balinese language through gending rare media in early childhood (3) the role of introducing Balinese language through gending rare media in early childhood at Hainan School Kindergarten. This research applies a qualitative approach, because it does not rely specifically on statistical data or numbers. The theories underlying this research include early childhood development theory and language development theory. The object of this research is focused on the role and function of rare gending media in introducing Balinese to young children. The research data source was obtained from the introduction of Balinese through rare gending at the Hainan School Kindergarten, using observation, interviews, literature study and documentation methods. The selection of informants was carried out using snowball sampling technique. The research results are known; (1) The learning strategies used in introducing Balinese through gending rare media for children at the Hainan School Kindergarten are audiovisual methods, picture methods, gending rare methods (movements and songs), and traditional game methods. (2) Inhibiting factors that influence the introduction of Balinese language in gending rare media in early childhood are the family environment, learning tools, the surrounding environment, as well as changes in culture and views of society. (3) some The role of introducing Balinese through gending rare media to children at the Hainan School Kindergarten is cultural preservation, character formation, and preservation of the mother tongue. In this context, the introduction of Balinese through the media of rare songs in early childhood has a very important role in preserving Balinese regional culture and language.